Domination without Dominance : Inca-Spanish Encounters in Early Colonial Peru - Lamana, Gonzalo, 1966- (Book collections on Project MUSE., 2008)
Complicates the Spanish conquest of Peru by seeking to overturn the interpretation made by 16th century Spanish writers and modern academics that cast the Inca-Spanish encounter as a battle between two clearly defined sides,